Study of Opportunities on Sharia-based Securities Instruments to Enhance the Economic Development in Indonesia - Arif Effendi (Cakrawala: Jurnal Studi Islam, 2018)
The purpose of Sharia Economics is to realize the goodness, prosperity, and prosperity of human beings, especially in the economic field. Islamic Sharia prohibits the practice of usury in all its economic activities, because of its negative impact on the social system and the economy of society. Article 1 of Law Number 19 Year 2008 stipulates that the State Sharia Securities or Sukuk, is state securities issued under sharia principles, so It must be free from various elements of the ban, such as usury, maysir, and gharar. Sukuk issuance aims to finance the State Budget, including financing the construction of projects, such as infrastructure projects in the energy sector, telecommunications, transportation, agriculture, manufacturing industry, and public housing. Therefore, the participation of Muslims as the majority in Indonesia are needed to become the investor. The method used in this article is librarian research. In describing, analyzing, and evaluating, we used the regulation concerning with state sharia securities in Indonesia such as Law Number 19 year 2008 and Fatwa of National Sharia Council No: 69/DSN-MUI/VI/2008 concerning State Sharia Securities. Participating as an investor in the State Sharia Securities means participating in developing the country